2021
DOI: 10.1080/15548627.2021.1922983
|View full text |Cite
|
Sign up to set email alerts
|

The human vault RNA enhances tumorigenesis and chemoresistance through the lysosome in hepatocellular carcinoma

Abstract: The small non-coding VTRNA1-1 (vault RNA 1-1) is known to confer resistance to apoptosis in several malignant cell lines and to also modulate the macroautophagic/autophagic flux in hepatocytes, thus highlighting its pro-survival role. Here we describe a new function of VTRNA1-1 in regulating in vitro and in vivo tumor cell proliferation, tumorigenesis and chemoresistance. Knockout (KO) of VTRNA1-1 in human hepatocellular carcinoma cells reduced nuclear localization of TFEB (transcription factor EB), leading to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 67 publications
1
31
0
Order By: Relevance
“…In HeLa cells, which derive from cervical adenocarcinoma, the knock out (KO) of the vtRNA1-1 lead to a significant decrease in cell proliferation [ 48 ]. The proliferation defect following a vtRNA1-1 KO was also observed in the hepatocellular carcinoma cell line Huh-7 [ 49 ]. In both KO cell lines, vtRNA1-1 was re-introduced in the genome by lentiviral transduction, and these vtRNA1-1 complemented cell lines rescued the growth defect [ 48 , 49 ].…”
Section: Vtrna1-1: Contributions To Cell Proliferation and Tumorigenesismentioning
confidence: 99%
See 4 more Smart Citations
“…In HeLa cells, which derive from cervical adenocarcinoma, the knock out (KO) of the vtRNA1-1 lead to a significant decrease in cell proliferation [ 48 ]. The proliferation defect following a vtRNA1-1 KO was also observed in the hepatocellular carcinoma cell line Huh-7 [ 49 ]. In both KO cell lines, vtRNA1-1 was re-introduced in the genome by lentiviral transduction, and these vtRNA1-1 complemented cell lines rescued the growth defect [ 48 , 49 ].…”
Section: Vtrna1-1: Contributions To Cell Proliferation and Tumorigenesismentioning
confidence: 99%
“…The proliferation defect following a vtRNA1-1 KO was also observed in the hepatocellular carcinoma cell line Huh-7 [ 49 ]. In both KO cell lines, vtRNA1-1 was re-introduced in the genome by lentiviral transduction, and these vtRNA1-1 complemented cell lines rescued the growth defect [ 48 , 49 ]. These studies revealed that, in cancer cells, vtRNA1-1 is an important proliferation factor and its absence impairs cell growth.…”
Section: Vtrna1-1: Contributions To Cell Proliferation and Tumorigenesismentioning
confidence: 99%
See 3 more Smart Citations